Sex differences in cognitive flexibility are driven by the estrous cycle and stress-dependent - Gargiulo, Andrew T.; Hu, Jiayin; Ravaglia, Isabella C.; Hawks, Annie; Li, Xinyue; Sweasy, Katherine; Grafe, Laura (Frontiers in Behavioral Neuroscience, 2022)
Stress is associated with psychiatric disorders such as post-traumatic stress disorder, major depressive disorder, anxiety disorders, and panic disorders. Women are more likely to be diagnosed with these stress-related psychiatric disorders than men. A key phenotype in stress-related psychiatric disorders is impairment in cognitive flexibility, which is the ability to develop new strategies to respond to different patterns in the environment. Because gonadal hormones can contribute to sex differences in response to stress, it is important to consider where females are in their cycle when exposed to stress and cognitive flexibility testing. Moreover, identifying neural correlates involved in cognitive flexibility could not only build our understanding of the biological mechanisms behind this crucial skill but also leads to more targeted treatments for psychiatric disorders. Although previous studies have separately examined sex differences in cognitive flexibility, stress effects on cognitive flexibility, and the effect of gonadal hormones on cognitive flexibility, many of the findings were inconsistent, and the role of the estrous cycle in stress-induced impacts on cognitive flexibility is still unknown. This study explored potential sex differences in cognitive flexibility using an operant strategy shifting-paradigm after either control conditions or restraint stress in freely cycling female and male rats (with estrous cycle tracking in the female rats). In addition, we examined potential neural correlates for any sex differences observed. In short, we found that stress impaired certain aspects of cognitive flexibility and that there were sex differences in cognitive flexibility that were driven by the estrous cycle. Specifically, stress increased latency to first press and trials to criterion in particular tasks. The female rats demonstrated more omissions and perseverative errors than the male rats; the sex differences were mostly driven by proestrus female rats. Interestingly, the number of orexinergic neurons was higher in proestrus female rats than in the male rats under control conditions. Moreover, orexin neural count was positively correlated with number of perseverative errors made in cognitive flexibility testing. In sum, there are sex differences in cognitive flexibility that are driven by the estrous cycle and are stress-dependent, and orexin neurons may underlie some of the sex differences observed.